Trophic and size structure of West Indian bird communities - Faaborg, John (1982)
Much discussion has occurred in recent years on whether observed patterns of structure in island bird communities are the result of competitive interactions among species or independent rates of colonization and extinction. Here two patterns of structure are presented for birds on 12 West Indian islands. Each of four major foraging guilds shows a distinct species-area pattern on the islands and saturation of species within habitats on larger islands. Frugivores have the steepest species-area curve and highest species numbers at saturation while nectarivores are lowest in both values. Coexisting guild members in saturated habitats are generally of different sizes, with weight differences by a factor of 2 common. On smaller islands, small guild members are absent and size differences among coexisting guild members may increase. In many cases, birds have apparently shifted size to conform to the structural patterns. The consistency of the patterns and variation within component species is highly compatible to explanations invoking competition and complements previously described population and community characteristics of West Indian birds.